Optimisation De La Stérilisation Des Conserves De Poisson Par La Mise Ne Place De La Démarche Six Sigma DMAIC - Idrissi, Ismail; Benazzouz, Bouchra (European Scientific Journal, ESJ, 2017)
The highly competitive economic environment has prompted companies to improve their industrial performance. In this context, an agrifood company seeks to improve the performance of its production resources as well as the quality system through the implementation of continuous improvement projects. The object of this work is the presentation of the results of the process of the improvement of industrial performance by the implementation of the Six Sigma approach on a process of sterilization of canned fish. To this end, the deployment of this project has made it possible to reduce the sterilizing value by 30% in order to improve the organoleptic qualities of the product. Also, the total duration of the heat treatments has been reduced by 20%, thus allowing a possible increase in productivity.